Therapeutic Potential of Nitrogen Mustard Based Hybrid Molecules - Chen, Yiming; Jia, Yuping; Song, Weiguo; Zhang, Lei (Frontiers in Pharmacology, 2018)
As medicine advances, cancer is still among one of the major health problems, posing significant threats to human health. New anticancer agents features with novel scaffolds and/or unique mechanisms of action are highly desirable for the treatment of cancers, especially those highly aggressive and drug-resistant ones. Nitrogen mustard has been widely used as an anticancer drug since the discovery of its antitumor effect in the 1942. However, the lack of selectivity to cancer cells restricts the wide usage of a mass of nitrogen mustard agents to achieve further clinical significance. Discovery of antitumor hybrids using nitrogen mustards as key functional groups has exhibited enormous potential in the drug development. Introduction of nitrogen mustards resulted in improvement in the activity, selectivity, targetability, safety, pharmacokinetics and pharmacodynamics properties of corresponding lead compounds or agents. Herein, the recently developed nitrogen mustard based hybrids have been introduced in the cancer therapy.